Strategi Optimalisasi Nikel Kadar Rendah untuk Ketahanan Cadangan Tambang di PT Koninis Fajar Mineral - Muhammad Najmi Ar Ramadan; Luky Patricia Widianingsih; William Santoso (Jurnal Manajemen dan Pemasaran Digital, 2026)
Indonesia possesses the world’s largest nickel reserves, which are heavily dominated by laterite ores consisting of high-grade saprolite and low-grade limonite. A long-standing over-reliance on saprolite accelerates the depletion of high-grade reserves and threatens the long-term sustainability of mining operations. In response to national downstreaming policies (Law No. 3/2020), mining companies are compelled to transform their operational governance. This study aims to analyze in depth the formulation, implementation, and critical success factors of low-grade nickel optimization strategies at PT Koninis Fajar Mineral (PT KFM). Adopting a qualitative approach with an exploratory-evaluative case study design, data were gathered through semi-structured in-depth interviews with strategic management and technical teams, field observations, and document analysis, which were subsequently analyzed using thematic analysis. The findings demonstrate that the low-grade nickel optimization strategy at PT KFM represents a systemic transformation from the traditional approach of grade maximization toward value-based mining and a variability-controlled system. The utilization of limonite ore successfully extends the mine life (resource longevity) and enhances reserve utilization. However, the successful implementation of this strategy is challenged by strategic tension between short-term production target pressures (throughput preservation) and the necessity of maintaining quality stability (quality preservation). The gap between planning and field execution is driven not only by geological uncertainty but also by operational system limitations that remain reactive, information fragmentation regarding quality data (QAQC time-lag), and human resource resistance at the field operator level. The novelty of this study lies in shifting the perspective of low-grade nickel optimization toward a socio-technical system approach that integrates the Resource-Based View (RBV) and Dynamic Capabilities theories, alongside formulating a three-phase transformation roadmap (Stabilization, Digitalization, and Proactive phases) that prioritizes change management enforcement. Keywords: nickel, low-grade, dynamic capabilities, systemic transformation